Ethical aspects of the work of a personal trainer - Kędzia, Piotr (Physical education, sport and olympism from a pedagogical perspective, 2023)
In recent years, the personal trainer profession has been characterised by high dynamics of development and exclusivity due to the individual form of work and the cost of the service. An important element of the trainer's wide range of competences is the ability to act ethically in working with the client. It is extremely important because the profession of a personal trainer consists mainly in direct contact with clients. The high ethical standards of the trainer strengthen their authority, build credibility and increase trust and consequently translates into the prestige of its own brand. In the course of improving the ethical efficiency of trainers, ethical codes also seem to be worth attention. Their assumptions are presented in the second part of the text. The aim of the article is to show the ethical aspects of the behaviour of personal trainers and their confrontation with accepted standards.